2013
DOI: 10.1002/jgra.50480
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the ionospheric E and F1 regions: Using SDO‐EVE observations as the solar irradiance driver

Abstract: [1] Over the altitude range of 90-150 km, in dayside nonauroral regions, ionization is controlled almost entirely by solar ultraviolet irradiance; the response time for ionization during solar exposure is almost instantaneous, and likewise, the time scale for recombination into neutral species is very fast when the photoionizing source is removed. Therefore, if high-resolution solar spectral data are available, along with accurate ionization cross sections as a function of wavelength, it should be possible to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…No values of plasma drift speeds or upward fluxes of plasma were presented. A follow‐up study by Sojka et al () used the same model with improved solar irradiance input to characterize flare effects in the lower ionosphere, with topside results similar to those in Smithtro et al (). Using a fully numerical global model (TIME‐GCM), Qian et al (, ) conducted simulations of ionospheric enhancements ( E layer and TEC) resulting from different locations of flares on the solar disk, as well as differences in flare rise and decay times.…”
Section: Model Resultsmentioning
confidence: 81%
“…No values of plasma drift speeds or upward fluxes of plasma were presented. A follow‐up study by Sojka et al () used the same model with improved solar irradiance input to characterize flare effects in the lower ionosphere, with topside results similar to those in Smithtro et al (). Using a fully numerical global model (TIME‐GCM), Qian et al (, ) conducted simulations of ionospheric enhancements ( E layer and TEC) resulting from different locations of flares on the solar disk, as well as differences in flare rise and decay times.…”
Section: Model Resultsmentioning
confidence: 81%
“…The wavelength range of ~0.4-5 nm is thought to contain the bulk of flare-radiated energy (Rodgers et al 2006) and is the primary driver of ionospheric dynamics. Very few spectrally resolved observations exist in this range, and the detailed dynamics depend critically on the altitude of energy deposition, strongly determined by the (unknown) spectral energy distribution (e.g., Sojka et al 2013). Our physically modeled DEMs allow generation of synthetic X-ray spectra in this unobserved passband, filling a crucial gap in the needed input for modeling of upper atmospheric behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Liu et al . [] found no interminima change in daytime electron densities at the E region peak ( N m E ), which is seemingly inconsistent with an interminima EUV irradiance decrease, since N m E responds positively to EUV, as well as to soft X‐rays [e.g., Sojka et al ., ]. Jee et al .…”
Section: Introductionmentioning
confidence: 99%
“…Araujo-Pradere et al [2011] reported interminima TEC decreases above four GPS receiver stations but found no systematic interminima N m F 2 change among four ionosonde stations. Furthermore, Liu et al [2011] found no interminima change in daytime electron densities at the E region peak (N m E), which is seemingly inconsistent with an interminima EUV irradiance decrease, since N m E responds positively to EUV, as well as to soft X-rays [e.g., Sojka et al, 2013]. Jee et al [2014] reported daytime interminima decreases in altimeter-derived, over-ocean TEC data, as well as offsetting nighttime increases that resulted in no net global change.…”
Section: Introductionmentioning
confidence: 99%